Investigating Iraqi EFL Students' Use of Social Learning Strategies (Journal of the College of Basic Education, 2022)
Learning strategies are actions taken by the learner to assist in learning more effectively, i.e., it may represent planning, competition, conscious manipulation, and movement toward a goal. Social strategies have a great importance in EFL learning since they increase the language learner opportunity to use the language for communication with activities such as: going to movies, reading books or talking to those who speak English very well, etc.This study aims at investigating Iraqi EFL students' use of social learning strategies. To achieve the aim of the study, the researchers have adopted a questionnaire that includes 30 items with the five point scale (always, usually, sometimes, rarely, never). The population of the study is fourth-year students at the Department of English/ College of Education for Women. The researchers applied the questionnaire on 80 students after modifying and changing certain items. In order to ensure the face validity, the questionnaire was exposed to a jury of experts in language and linguistics who agreed upon its validity and suitability. Twenty students were randomly chosen for the pilot study which revealed that the time needed to complete the questionnaire items was 45 minutes. As for the clarity of the items, it was noticed that most of the items were clear and the students found no difficulty in answering the questionnaire items. As for reliability, the items were divided into two halves (odd and even). Using the Pearson correlation formula, it is found out that the questionnaire reliability is 0.754. After applying the Spearman Brown formula, it was found out the questionnaire reliability is 0.859. This shows that the questionnaire is quite reliable and acceptable.Using the Fisher's formula to manipulate the data statistically and establish the weighted mean for each item, it is proved that the participants use all the types of social strategies but with different weights. Some items of all the strategies (Asking questions, Cooperating with others, Empathizing with others, Seeking opportunities) are proved to be weak or unused by some of the students, such as items (8, 12, 17, 18, 19, 23, 26, 27, 28 and 29). At the end, conclusions, recommendations, and suggestions for further studies are put forward